2011
DOI: 10.5713/ajas.2011.10441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xylanase Supplementation on the Net Energy for Production, Performance and Gut Microflora of Broilers Fed Corn/Soy-based Diet

Abstract: The objective of this study was to assess the effect of xylanase on net energy for production, performance, nutrient digestion and gut microflora of broilers fed corn/soy-based diet. Eighty-four day-old male broiler chicks were allocated to two groups receiving two treatments, respectively. Each treatment had six replicate cages with seven broilers per cage. The diets were based on corn and soybean. The treatments were: i) basal diet reduced in apparent metabolizable energy (-0.63 MJ/kg compared to commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 13 publications
5
18
1
Order By: Relevance
“…Meanwhile, xylanase supplementation reduces the detrimental effects of arabinoxylans and increases digestibility of N and GE. The improvement in digestibility observed in this study was consistent with the results of Nian et al () and Passos et al (), who reported that the supplementation of xylanase in corn‐soybean meal based diet improved ileal digestibility of DM, organic matter, GE, neutral detergent fiber and crude ash. The improvement in ATTD of DM, N and GE with xylanase supplementation can, in turn, induce a significant increase in the ADG and G:F. These findings, combined with the improvement in growth performance with supplementation of 0.01% xylanase to corn‐soybean meal based diet in this study, suggested that the use of xylanase exerted a beneficial effect on weaning pig performance when a corn‐soybean meal based diet is used.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, xylanase supplementation reduces the detrimental effects of arabinoxylans and increases digestibility of N and GE. The improvement in digestibility observed in this study was consistent with the results of Nian et al () and Passos et al (), who reported that the supplementation of xylanase in corn‐soybean meal based diet improved ileal digestibility of DM, organic matter, GE, neutral detergent fiber and crude ash. The improvement in ATTD of DM, N and GE with xylanase supplementation can, in turn, induce a significant increase in the ADG and G:F. These findings, combined with the improvement in growth performance with supplementation of 0.01% xylanase to corn‐soybean meal based diet in this study, suggested that the use of xylanase exerted a beneficial effect on weaning pig performance when a corn‐soybean meal based diet is used.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we observed an improvement in gut microflora by supplementation of broiler diet with EP, which was in agreement with Nian et al (2011), who found that lactobacilli and bifidobacteria counts increased with the supplementation of xylanase in broilers. Bedford (2000) also showed that exogenous enzymes could alter microbial populations indirectly within the GI tract through their utilisation of the substrates that bacteria use as a carbon source.…”
Section: Discussionsupporting
confidence: 92%
“…Xylanase supplementation has been shown to be beneficial to the performance of feed-restricted broilers (Pinheiro et al 2004). Nian et al (2011) also demonstrated that the addition of xylanase to a corn-soybean-based diet in broilers significantly improved feed energy as well as FCR. This improvement could be due to the ability of NSPase to break down the encapsulation of starch and proteins in botanical resources.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Contrary to the expectations, xylanase resulted in increased numbers of Clostridium in birds fed diets with both fat sources. The present results are in contrast with those of Nian et al (2011) who reported that birds fed soybean oil diets supplemented with xylanase had higher caecal counts of Lactobacillus than those fed diets without xylanase. Choct et al (2004) also reported that xylanase supplementation of wheat-based diets reduced the numbers of Clostridium perfingens in caecal contents.…”
Section: Discussioncontrasting
confidence: 99%